“You Come for the Cause and Stay for the People”: A Grounded Theory Case Study of Mission Internalization Through a Ducks Unlimited Event - Kemink, Kaylan M.; Cavanah, Sarah; Ellis-Felege, Susan; Felege, Christopher (Journal of Leadership, Accountability and Ethics, 2023)
Retaining professional and skilled employees in the non-profit sector is often dependent on facilitating the internalization of an organization’s mission. This case study of a mission-based event for a conservation organization examines how participants expressed dimensions of mission internalization described by Marimon, Mas-Machuca, and Rey (2016: Importance, Leadership, Knowledge, and Co-worker engagement). Through pre-event survey responses, a post-event focus group, and follow-up interviews, participants expressed how the experience created aspects of mission internalization. An informed grounded theory analysis helped to identify common concepts among participants. Further analysis suggested these concepts helped to build themes like Importance, Knowledge and Co-worker engagement and indicated a new dimension of Organizational Capital. However, participants noted a lack of leadership presence, and expressed some concerns about the overabundance of Knowledge they were presented with during the event. This lack of leadership presence and emphasis on Knowledge may affect the process of mission internalization. Suggestions for more work in this relatively unexplored field to further understand mission internalization in conservation-based non-profits are provided.